Research on the Evolution Characteristics of Building Space in the Central Urban Area of Tianjin Based on Multi-Source Data Collaboration: 2021–2024 - Yicheng Zhang; Guorui Chen; Xue Yang (Buildings)
Urban renewal faces critical challenges in balancing heritage protection and functional upgrades, particularly in dual-attribute cities like Tianjin that preserve industrial legacy while cultivating emerging functions. Existing studies exhibit three gaps: geographical bias toward megacities, fragmented analysis of functional–morphological interactions, and inadequate quantification of “protection-development” tensions. This study addresses these gaps through an integrated framework combining point-of-interest kernel density analysis and satellite imagery segmentation (2021–2024 data). The methodological innovations include: (1) Analysis of urban function changes based on Point of Interest density; (2) Analysis of urban spatial morphology changes based on the texture of buildings within plots; (3) Spatiotemporal coupling analysis of data. Key findings reveal: (a) The overall Point of Interest density in Tianjin increased by 127.2%, achieving further prosperity and development of the city; (b) The renewal of the central urban area exhibits characteristics of “edge aggregation and gradient diffusion”; (c) The historic urban area has reshaped its functional layout through micro-renewal and the relocation of industrial spaces, effectively balancing the conflict between preservation and development. This study systematically summarizes the experiences in resolving the conflict between preservation and development in the urban renewal of Tianjin, providing a reference case for cities undergoing similar dual-attribute renewal.